2022
DOI: 10.1039/d1ew00870f
|View full text |Cite
|
Sign up to set email alerts
|

The regenerative role of biofilm in the removal of pesticides from stormwater in biochar-amended biofilters

Abstract: Low-impact, green infrastructure systems such as biofilters, particularly when amended with biochar, can help address chemical pollution conveyed via stormwater that is increasingly posing a threat to aquatic ecosystems and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 104 publications
0
22
0
Order By: Relevance
“…Past studies on use of BC such as biochar or AC for stormwater treatment have investigated a limited range of conditions, including low flow rates, relatively fine particle sizes, and few co-contaminants. , As reported in Table , recent studies have employed low flow rates of several cm hr –1 and grain sizes typically less than 800 μm. Slow treatment flow rates would require larger SCM foot prints to hold and treat all of the stormwater runoff and are not necessarily representative of typical design guidance which specifies infiltration rates in the range of 7–22 cm hr –1 for stormwater runoff treatment. , Increasing the flow rate necessitates increased particle sizes to facilitate hydraulic conductivity and results in shorter contact times, both of which are expected to negatively affect contaminant removal kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies on use of BC such as biochar or AC for stormwater treatment have investigated a limited range of conditions, including low flow rates, relatively fine particle sizes, and few co-contaminants. , As reported in Table , recent studies have employed low flow rates of several cm hr –1 and grain sizes typically less than 800 μm. Slow treatment flow rates would require larger SCM foot prints to hold and treat all of the stormwater runoff and are not necessarily representative of typical design guidance which specifies infiltration rates in the range of 7–22 cm hr –1 for stormwater runoff treatment. , Increasing the flow rate necessitates increased particle sizes to facilitate hydraulic conductivity and results in shorter contact times, both of which are expected to negatively affect contaminant removal kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…These features would theoretically lead to higher sorption affinity, especially for organic compounds that contain multiple moieties. 73 Finally, our results demonstrated that the four primary tire rubber-derived compounds often underwent desorption hysteresis and the higher the aqueous concentration, the stronger the hysteretic effect. Over the long term, processes like irreversible sorption and transformation are the ultimate sinks of these chemicals.…”
Section: ■ Conclusionmentioning
confidence: 58%
“…Biochar is also often utilized to remove contaminants from stormwater; it is relatively more porous and contains more functional groups compared with natural soils. These features would theoretically lead to higher sorption affinity, especially for organic compounds that contain multiple moieties …”
Section: Discussionmentioning
confidence: 99%
“…14 Sorption and tortuosity parameters, critical for describing contaminant sorption and effective intraparticle diffusion, have been determined using batch isotherms 10 or by fitting the transport model to observed contaminant migration. 11,13 The model, fit to or using experimental data, has then been used to estimate BC filter performance in the field. 11,13 However, use of the sorption-retarded intraparticle pore diffusion model for predicting TrOC transport in BC-amended engineered media stormwater filters has been constrained by model limitations and experimental conditions and seldom incorporated validation.…”
Section: Introductionmentioning
confidence: 99%
“…11,13 The model, fit to or using experimental data, has then been used to estimate BC filter performance in the field. 11,13 However, use of the sorption-retarded intraparticle pore diffusion model for predicting TrOC transport in BC-amended engineered media stormwater filters has been constrained by model limitations and experimental conditions and seldom incorporated validation. While variable influent concentration has recently been incorporated into the model, 11 further implementation of variable flow rate is necessary for situations when contaminant removal is kinetically limited and thus flow rates through the filter may impact contaminant removal.…”
Section: Introductionmentioning
confidence: 99%